KORELASI COGNITIVE SKILL DAN KEMAMPUAN BAHASA INGGRIS TERHADAP PEMAHAMAN TERMINOLOGI BAHASA INGGRIS PADA PROGRAM STUDI AKUNTANSI PERPAJAKAN - Fajar Pudo; M.A, Abdul Malik (Journal of Economic, Bussines and Accounting (COSTING), 2026)
As part of efforts to compete in the global economy and business arena, several universities have begun integrating English terminology into their learning processes. One such institution is the Tax Accounting Program at Politeknik Baubau. However, introducing and applying this terminology has not been immediately easy for students to accept and internalize. Therefore, it is important to examine students’ acceptance and understanding of English terminology in Economics and Business. This study aims to investigate the relationship between cognitive skills and English language proficiency in influencing students’ ability to comprehend English terminology at Politeknik Baubau’s Tax Accounting Program. Using qualitative research methods with a descriptive approach, the study systematically and accurately describes the relationships between variables and the phenomena observed. Data collection for these three variables was conducted through tests, observations, and interviews, followed by detailed analysis to explore the reciprocal relationships among them. The researcher served as the primary instrument in collecting and processing the data, ensuring higher accuracy. The study found that students’ cognitive skills test scores and their English terminology comprehension scores were both relatively low and displayed similar patterns. Further analysis indicated that these low scores were largely caused by misunderstandings and mistakes in interpreting the material.